Malaria Cell Image Classification Using Compact Deep Learning Architectures on Jetson TX2 - Alonso-Ramírez, Adán-Antonio; Méndez-Gurrola, Iris Iddaly; Barranco-Gutiérrez, Alejandro-Israel; Gutiérrez-López, Marcos; Prado-Olivarez, Juan; Pérez-Pinal, Francisco-Javier; Villegas-Saucillo, J. Jesús; García-Muñoz, Jorge-Alberto; García-Capulín, Carlos-Hugo (2024)
Malaria is a significant global health issue, especially in tropical regions. Accurate and rapid diagnosis is critical for effective treatment and reducing mortality rates. Traditional diagnostic methods, like blood smear microscopy, are time-intensive and prone to error. This study introduces a deep learning approach for classifying malaria-infected cells in blood smear images using convolutional neural networks (CNNs); Six CNN models were designed and trained using a large labeled dataset of malaria cell images, both infected and uninfected, and were implemented on the Jetson TX2 board to evaluate them. The model was optimized for feature extraction and classification accuracy, achieving 97.72% accuracy, and evaluated using precision, recall, and F1-score metrics and execution time. Results indicate deep learning significantly improves diagnostic time efficiency on embedded systems. This scalable, automated solution is particularly useful in resource-limited areas without access to expert microscopic analysis. Future work will focus on clinical validation.